The Association Between COVID-19 and Thyroxine Levels: A Meta-Analysis - Chen, Yiru; Li, Xiuneng; Dai, Yu; Zhang, Jingjing (Frontiers in Endocrinology, 2022)
Objectives: Recently, a number of reports have described the potential relationship between COVID-19 and thyroid hormones, but the results were conflicting. We performed a meta-analysis to evaluate the effect of the severity of COVID-19 on thyroid-related hormones and the effect of thyroid-related hormones on the outcome of COVID-19 in order to try to confirm the association between the serum levels of free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) and the severity or mortality of coronavirus-19 patients. Methods: The methodology was already registered in the International Prospective Register of Systematic Reviews (PROSPERO) database, and the protocol number is CRD42021269246. Systematic searches were carried out on the Cochrane Library, Embase, PubMed and Web of Science databases on November 15, 2021. We set up the literature search strategy based on the following keywords: [(T3 OR FT3 OR triiodothyronine) or (T4 OR FT4 OR thyroxine) or (TSH or thyrotropin)] and (COVID-19 OR SARS-CoV-2), without time restrictions. Results: Twenty studies satisfied the inclusion/exclusion criteria and were included in the meta-analysis. A total of 3609 patients were enrolled in the study. From the analysis of the included studies, the incidence of thyroid-related hormone abnormalities was higher in patients with severe COVID-19, and the serum levels of FT3 and TSH were lower than those of patients with nonsevere COVID-19. However, the difference in the FT4 levels was not significant. Similar characteristics were shown between survivors and nonsurvivors. In addition, the outcomes of the meta-analysis showed that patients with abnormal thyroid-related hormones had greater mortality. Conclusions: Low FT3 serum levels, low FT4 serum levels and low TSH serum levels may increase the mortality of COVID-19 patients during admission. On the other hand, the higher the severity level of COVID-19, the higher the probability of decreases in the FT3, FT4, TSH levels.